Neonatal meconium aspiration syndrome associated with ABCA3 gene mutation and mycoplasma infection: a case report - Oliver Stelzig; Beatrix Mühlegger; Anna Zschocke; Ursula Kiechl-Kohlendorfer; Elke Griesmaier (BMC Pediatrics)
Abstract Preterm infants are at high risk of developing respiratory distress syndrome (RDS). Mutations in the genes encoding for surfactant proteins B and C or the ATP-binding cassette transporter A3 (ABCA3) are rare but known to be associated with severe RDS and interstitial lung diseases. The exact prevalence of these mutations in the general population is difficult to determine, as they are usually studied in connection with clinical symptoms. Most cases are not captured due to variability in expression or diagnosis. It is estimated that they affect a small percentage of the population, with mutations in ABCA3 most commonly identified in association with severe lung diseases in newborns. Even heterozygous ABCA3-mutations can increase the risk and severity of RDS in neonates. The expression of these proteins is developmentally regulated, increases with gestational age, and is crucial for the function of pulmonary surfactant at birth. Additional lung stressors, such as meconium aspiration syndrome or pulmonary infections, can lead to a complex clinical picture associated with severe courses. This case report describes an extremely preterm female infant with suspected meconium aspiration syndrome, severe RDS, Mycoplasma pneumoniae infection, and a heterozygous ABCA3-mutation. The report discusses the clinical presentation, diagnostic evaluation, and therapeutic interventions, emphasizing the complexities associated with multiple pulmonary conditions in the context of extreme prematurity. At the limits of viability, therapeutic options for severe respiratory insufficiency are limited compared to older children. The developmental neurological prognosis following prolonged relative hypoxia is a crucial factor to consider in discussions about changing treatment goals. Particularly in severe cases, pulmonary infections and genetic changes in surfactant metabolism must be considered in newborns with RDS.